Human Remains Disposal and Ritual Killings in Nigeria: A Comparative Analysis of Nigerian Criminal Law and Islamic Legal Principles - Yusuph, Ismael Funsho; O. Afolabi, Solomon; Taofeeq Abolaji, Abdulraheem (Universitas Islam Negeri Alauddin Makassar, 2026)
The right to life and the dignity of the human person are protected under Nigerian law and Islamic jurisprudence. Nonetheless, Nigeria continues to witness a disturbing rise in ritual killings, often accompanied by mutilation and the degrading disposal of corpses in bushes, rivers, shallow graves, and refuse sites. While homicide is clearly criminalised, Nigerian criminal law, particularly under the Penal Code, contains weak, fragmented, or absent provisions regulating the disposal of human remains, thereby creating enforcement gaps that impede effective investigation and prosecution. This study adopts a doctrinal and comparative legal methodology by analysing relevant provisions of Nigerian criminal law, including the Criminal Code, the Penal Code, and selected state legislation, alongside classical and contemporary Islamic legal principles governing the treatment and burial of the dead. Judicial decisions, statutory texts, and secondary literature are examined to assess normative standards and enforcement implications. The study finds that Nigerian law inadequately addresses the offence of improper disposal of corpses, treating it, at best, as peripheral misconduct rather than as a distinct and serious crime. In contrast, Islamic law imposes strict obligations of prompt and respectful burial and prescribes discretionary or aggravated sanctions where post-mortem dignity is violated. This article contributes to existing scholarship by systematically identifying legal gaps in Nigeria’s corpse disposal regime and demonstrating, through comparative analysis, how Islamic legal principles offer a coherent normative framework for protecting post-mortem dignity, thereby providing a principled basis for reform discussions within Nigeria’s plural legal system, particularly in addressing ritual killings and related investigative challenges.